2018
DOI: 10.1182/blood-2018-168
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Cell Transplantation in Thalassemia and Sickle Cell Disease: Report from the European Society for Blood and Bone Marrow Transplantation Hemoglobinopathy Registry: 2000-2017

Abstract: INTRODUCTION: Allogeneic hematopoietic cell transplantation (HCT) is a diffuse curative option for transfusion dependent thalassemia (TDT) and sickle cell disease (SCD). To verify transplant activity, distribution, demography, policies and outcomes the Hemoglobinopathy Registry was established inside the European Group for Blood and Marrow Transplantation (EBMT). After a previous analysis limited to TDT for the 2000-2010 period data (BMT 2016; 51:536-41), we performed an updated report considering TDT and SCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Thus, the aberrant vascular niche might also reduce HSPC homing and engraftment efficiency during HSC transplantation of SCD patients, in particular older SCD patients or those with chronic sickle cell-related endorgan damage. 21,78 Given the pathogenic role of sickle RBCs in the BM vasculopathy of SCD, we reasoned that weekly transfusion of healthy RBCs for 6 weeks to reduce HbS levels to ,30% might beneficially impact the BM vascular niche in SCD mice. Indeed, we found that this transfusion regimen reverses BM vascular niche structural defects ( Figure 7) and splenomegaly ( Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aberrant vascular niche might also reduce HSPC homing and engraftment efficiency during HSC transplantation of SCD patients, in particular older SCD patients or those with chronic sickle cell-related endorgan damage. 21,78 Given the pathogenic role of sickle RBCs in the BM vasculopathy of SCD, we reasoned that weekly transfusion of healthy RBCs for 6 weeks to reduce HbS levels to ,30% might beneficially impact the BM vascular niche in SCD mice. Indeed, we found that this transfusion regimen reverses BM vascular niche structural defects ( Figure 7) and splenomegaly ( Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Bei Vorhandensein eines HLA-identischen verwandten Spenders gilt sie bei Patienten mit Thalassaemia major als Therapie der Wahl 4 10 . Die publizierten Daten zur HSZT von einem nicht verwandten HLA-identischen Spender zeigen, dass sie für Patienten ohne verwandten Spender eine geeignete Therapieoption sein kann 17 . Eine HSZT von HLA-haploidentischen Spendern ist möglich, aktuell jedoch noch nicht generell zu empfehlen 4 10 .…”
Section: Beta-thalassämienunclassified
“…Data from the European Hemoglobinopathies Registry show that patients aged <14 years with an HLA-identical family donor have an overall survival rate of 91.9% and thalassemia-free survival of 86%. 9 , 28 Recently, experiences evaluating transplantation with matched unrelated donors and haploidentical donors in patients with β-TDT have been published with relevant results. 8 , 29 , 30 …”
Section: Allogeneic Transplantationmentioning
confidence: 99%